2016
DOI: 10.1111/1471-0528.13992
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year effects and cost‐effectiveness of pelvic floor muscle training in mild pelvic organ prolapse: a randomised controlled trial in primary care

Abstract: Pelvic floor muscle training can be effective in women with bothersome symptoms of mild prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 32 publications
0
36
0
4
Order By: Relevance
“…POP is a serious public health problem that affects sexual function, quality of life, and psychological state; however, it is generally ignored by women. It was reported in that POP affected sexual function and life quality of women negatively ( 8 , 9 , 10 , 11 ) . However, a limited number of studies have contributed data regarding how women are affected by POP in relation to the prolapse compartment ( 12 , 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…POP is a serious public health problem that affects sexual function, quality of life, and psychological state; however, it is generally ignored by women. It was reported in that POP affected sexual function and life quality of women negatively ( 8 , 9 , 10 , 11 ) . However, a limited number of studies have contributed data regarding how women are affected by POP in relation to the prolapse compartment ( 12 , 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Hierbei Eine Beckenboden-Rehabilitation durch die Behandlung mittels Physiotherapie sowie eine Biofeedback-und Elektrostimu-lationstherapie können helfen, die Symptome zu lindern, das Prolapsstadium zu reduzieren bzw. die Progression der Senkung verhindern [9,10].…”
Section: Discussionunclassified
“…The randomized trial by Panman et al found that PFPT was superior to expectant management in that women who underwent PFPT had a 12.2‐point increase (95% CI, 7.2‐17.2; P < .001) in the score on the validated Pelvic Floor Distress Inventory . In one randomized controlled trial, 39% of women with pelvic organ prolapse receiving PFPT reported improved sexual function compared with 5% of women in the control group ( P < .01).…”
Section: Pelvic Organ Prolapsementioning
confidence: 99%